Effect of Working Capital, Asset Turnover and Sales Growth Limited Return on Assets on Food and Beverage Industry - Jumeida Simatupang; Eka Purnama Sari (International Journal of Business Economics (IJBE), 2021)
This study uses financial management theory related to variable Return On Assets, Working Capital, Asset Turnover and Sales Growth. The approach used is an associative approach. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange IDX period 2017-2019. Samples were taken using multiple linear regression analysis methods, classic assumption test, t test (partial test), f test (simultaneous test) and SPSS 24.0 software assistance determination coefficient (Statistical Product and Service Solution). So obtained 12 companies as samples. The results showed that: Working Capital has no significant effect on Return On Asset, Asset Turnover has no significant effect on Return On Asset, while Sales Growth also has no significant effect on Return On Asset. And simultaneously Working Capital, Turnover Assets and Sales Growth has no effect and is insignificant to Return On Asset.